Pendampingan Penyusunan Laporan Keuangan Dan Strategi Pemasaran UMKM Kerupuk Udang Dan Ikan Payus Mak Sah - Femy Atha Fredella; Bagus Ariz Faishal; Risqi Firdaus Setiawan; Praja Firdaus Nuryananda (Politeknik Kampar, 2023)
The purpose of preparing financial reports and marketing strategies is to increase knowledge of the importance of existing cash flows. The assistance provided forms independent umkm. The independence of umkm has the potential to develop its market through the marketing strategy that has been given. The marketing strategy is a tool that supports business decision making for UMKM